Kinetics of the early growth of actinomycete streptomyces coelicolor - Kotov, V.; Korol, Anatoliy (My University, 1989)
Various growth characteristics of Streptomyces coelicolor are considered and numerous relations among them are discussed. An attempt is made to tie the events at the hyphal level to an understanding of phenomena at the organism level. The results are presented as corollaries of a theoretical model based on a special atochastic branching process involving apices of three types. Theoretical conclusions are compared to the experimental data on growth and branching of colonies of S.coelicolor from paper.
Keywords: hyphal level; актиноміцети; branching process; гіфальний рівень; розгалужені процеси; кафедра фізики та професійної безпеки